THU0726-HPR Adherence to biological therapy in chronic inflammatory rheumatism: results of a retrospective study in auvergne, france. (12th June 2018) - Fayet, F.; Rodere, M.R.; Savel, C.; Pereira, B.; Soubrier, M.; Couderc, M.
Abstract : Background: The arsenal of treatment options for Chronic inflammatory rheumatism (CIR) has considerably grown over recent years with the biological therapies. Poor patient adherence to treatment is a major barrier to proper disease management. Patient education enhances drug adherence by improving the knowledge and skills needed to manage the disease and treatments. Objectives: This study aimed to assess adherence to subcutaneous biological therapy using the Morisky Medication Adherence Scales (MMAS-4) in patients with CIR: rheumatoid arthritis (RA), ankylosing spondylitis (SA) and psoriatic arthritis (PsA), who received education in our department. Methods: This was a retrospective single-centre observational study of routine care. All patients on subcutaneous biological therapy who received at least one education interview between 2009 and 2013 were included. Adherence was assessed using the Morisky questionnaire (MMAS-4). A comparison of adherence was made based on the BIOSECURE questionnaire (knowledge and skills relating to biological therapy) and type of educational model received by patient (model 1: providing information; model 2: performing one-on-one education; model 3: performing head to head and group-based education). Adherence was also compared based on population characteristics, type of care (mixed or solely hospital), type of CIR, number of education interviews, injection frequency and type of biological therapy. Results: A total of 193 patients were included in the study, 124 of whom were women. The population's mean age was 53.3±14.8 years. Patients had had CIR for 10 years, 5–18 with 113 patients suffering from RA, 73 from SA, and 7 from PsA. Of the 193 patients, 192 (99.5%) were on TNF inhibitors (of whom 107 [55.4%] were on etanercept, 58 [30.1%] on adalimumab, 10 [5.2%] on certolizumab and 17 [8.8%] on golimumab) while 1 (0.5%) was on abatacept. About 75.7% (n=146) of the patients reported good adherence (Morisky=0), 17.6% (n=34) moderate adherence (Morisky=1 or 2), and 6.7% (n=13) poor adherence (Morisky=3 or 4). No significant association was observed between knowledge and skill levels as evaluated by the BIOSECURE questionnaire and adherence as evaluated by the Morisky questionnaire (respectively, 76±13, 77±11, 76±18, p=0.91). A total of 92 patients received model 1, 80 received model 2, and 21 received model 3. Adherence was poorer in the group that received model 3 compared with the other two models (79% Morisky score of 0 for model 1, 76% for model 2 versus 57% for model 3; p=0.04) and poorer in young patients (p=0.005). No difference existed based on gender, education level, marital status, type of care (mixed or solely hospital), type of CIR, number of education interviews, frequency (1, 2 or 4 weeks) of biological injections. Conclusions: Adherence to biological therapy was quite good in this study. No link existed between adherence and knowledge levels. Combining head to head and group-based patient education did not improve adherence compared with simply providing information or performing head to head patient education alone. Disclosure of Interest: None declared